Web-based publication management system for I-idea / Nik Nurul Huda Nik Azmi - Nik Azmi, Nik Nurul Huda (2020)
IDeA is one of the competitions for the students who have innovation to produce their own ideas. In i-IDeA, the participants can develop their own idea and it can be published online. Innovation is a creating of new ideas to produce the products as new businesses and it is a very important source of evaluation in business. Besides, while creating the innovation, the participants who involve in the i-IDeA competition, can produce their own paper as publication. Therefore, there are several issues faced by participants when they need to submit the paper manually via email. Based on this issue, this system chooses to use web-based application to hone and help the administrator and participants solve the problems that they have been faced. This project is developed using Laravel framework, MySQL and Visual Studio Code. Besides, the evaluation phase consists of functionality testing and technology acceptance model (TAM) which have three components which are Perceived Usefulness, Perceived Ease of Use and User Satisfaction. This system is helpful for i-IDeA because the interface of this system is very practical and the flow this system is easy to understand. Besides, PUMS provides a few main functions for the administrator and participants and it also helps the i-IDeA to handle the publication process in an effective way. Lastly, web-based technology is also important because it has a lot of benefits for organization that applied the web-based application in their organization especially to provide the publication in web-based application for i-IDeA.